PENINGKATAN KUALITAS PRODUK DAN PERLUASAN PASAR KERIPIK SINGKONG "ENSI" DI DESA TEGALSARI, KECAMATAN AMBULU, KABUPATEN JEMBER - Widaninggar, Nanda; Amin, Saiful; Sari, Nurshadrina Kartika (JURNAL PENGABDIAN MASYARAKAT (JPM), 2022)
Tegalsari Village is located in Ambulu District, Jember Regency. The people's livelihood is generally in agriculture, either as farmers, farm laborers, as well as casual daily laborers and animal husbandry. In September 2021 a new young entrepreneur was formed, named Chips "ENSI". These chips are marketed directly to end users, through the Pre-Order mechanism or based on orders, but the number of sales has not been in accordance with the target, even though it has been able to cover the initial capital issued. In addition, there are problems in obtaining good quality cassava which results in a decrease in the quality and quantity of production and product packaging design. Based on this situation analysis, the main problem in the target community is the need for assistance to new young entrepreneurs of cassava chips, which is carried out through the selection of product raw materials, product processing, product innovation, packaging design and marketing (marketing strategy). The implementation of Community Service activities in the form of product raw material selection, product processing, Product Innovation, packaging design and marketing (marketing strategy) in Tegalsari Village, Ambulu District, Jember Regency went well and smoothly, and received full support from the surrounding environment. Finally, "ENSI" cassava chips have become a quality product and are very worthy of being marketed, because they taste good, have attractive packaging, and are affordable. New marketing strategies need to be implemented to face increasingly fierce competition.